Integrating Knowledge Management and the Kodály Method in Teaching Chinese Traditional Music to Primary Students - Zhihui, Ni; Supattarachiyawong, Watcharapong (International Journal of Multidisciplinary in Management and Tourism, 2025)
This article focuses on Knowledge Management for Chinese Traditional Music through the Kodály Method. The research investigated teaching practices and knowledge management in upper primary music classrooms at Dinglan Third Primary School, Shangcheng District, Hangzhou, Zhejiang, China. The study population consisted of Grade 4–6 students, with approximately 30 students per class. The research employed qualitative methods, using semi-structured academic interviews and classroom observations as primary tools for data collection. The researcher conducted classroom observations over a period of 16 weeks. The findings revealed that the music teacher incorporated three Chinese traditional songs: Dongting Lake, Little Flying Dance, Victory Celebration. These three songs focus on classroom instruction using the Kodály teaching method, developing five types of exercises: Rhythm Exercises, Sight-singing Exercises, Aural Training Exercises, Hand Signs Exercises, and Composition Exercises. The teacher effectively integrated Kodály's pedagogical principles with traditional folk music content. The study applied a five-step knowledge management process to structure the instructional approach: 1. Identifying – determining key knowledge relevant to the subject, 2. Acquiring – gathering and expanding knowledge through internal and external sources, 3. Storing – systematically organizing the acquired knowledge, 4. Sharing – disseminating and communicating knowledge effectively, and 5. Applying – putting the knowledge into practice within the classroom setting Knowledge management in the music classroom at Dinglan Third Primary School was found to be effective. The school successfully applied Chinese folk music knowledge to the Kodály teaching method in a systematic and structured manner, resulting in an effective solution to the challenges of teaching folk song performance in the classroom.